Liesegang Phenomenon of Liquid Metals on Au Film (Adv. Mater. 7/2023). Issue 7 (19th February 2023) - Xing, Zerong; Zhang, Genpei; Ye, Jiao; Zhou, Zhuquan; Gao, Jianye; Du, Bangdeng; Yue, Kai; Wang, Qian; Liu, Jing
Abstract : Liquid Metal Liesegang Rings In article number 2209392, Qian Wang, Jing Liu, and co‐workers investigate the Liesegang rings phenomenon induced by gallium‐based liquid metal (LM) on gold film systems. The mechanisms are attributed to the reaction‐diffusion and spreading‐limiting processes of the LM on gold film, over which chemical reactions occur simultaneously with the spatially recurrent crystallization of intermetallic compounds AuGa2 and AuIn2 . This discovery has generalized purpose and can serve as a flashpoint for tackling diverse self‐organized reaction‐diffusion systems between LMs and various solid metal films.